PENGARUH PEMAHAMAN SISWA DALAM MENYUSUN JURNAL UMUM TERHADAP KEMAMPUAN SISWA MEMBUAT NERACA SALDO PADA MATA PELAJARAN AKUNTANSI DI KELAS X SMK.T AMIR HAMZAH TANJUNG KUBAH INDRAPURA T.A 2022/2023 - Bella Atika; Rijal Rijal (Jurnal Inovasi Penelitian, 2023)
This study uses a type of quantitative research. The sample used in this study amounted to 32 people, using the total sampling technique. The purpose of this research is to find out whether students' understanding of compiling general journals affects students' ability to make trial balances in accounting class X SMK.T Amir Hamzah Tanjung Kubah Indrapura. This study used instruments in the form of test questions and documentation. The results of this study showed that the value of tcount was 0.9 while the magnitude of ttable at a significant level of 0.05 with dk = n – 2 = 32 – 2 = 30 was 1.697. Therefore t_count ≤ t_table or 0.9 ≤ 1.697 where the alternative hypothesis is accepted (Ha) and the observation hypothesis (Ho) is rejected, so the hypothesis in this study can be accepted as true. The conclusion of this study is that there is an influence of students' understanding in compiling general journals on students' ability to make trial balances for class X2 Accounting SMK.T Amir Hamzah Tanjung Kubah Indrapura